Graphic Design and Trends in Globality - Guerrero, Manuel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Graphic design is a discipline that continuously adapts to economic, social, and technological contexts, which keeps some correspondence to the way of thinking. The structure of this text consists of three parts. The first one deals with the definition of graphic design as a discipline and the way it has evolved, then explains the relationship it has with the visual paradigm that originated it, and finally, understand through the visualization of trends how graphic design has been adapting to the global context.